Indigenous Peoples' evaluation of health risks when facing mandatory evacuation for birth during the COVID-19 pandemic: an indigenous feminist analysis - Melanie Murdock; Erika Campbell; Sarah Durant; Carol Couchie; Carmel Meekis; Charitie Rae; Julie Kenequanash; Arthi Erika Jeyamohan; Jacob Barry; Lisa Boivin; Karen Lawford (BMC, 2024)
Abstract Background Indigenous Peoples living on the land known as Canada are comprised of First Nations, Inuit, and Métis people and because of the Government of Canada's mandatory evacuation policy, those living in rural and remote regions of Ontario are required to travel to urban, tertiary care centres to give birth. When evaluating the risk of travelling for birth, Indigenous Peoples understand, evaluate, and conceptualise health risks differently than Eurocentric biomedical models of health. Also, the global COVID-19 pandemic changed how people perceived risks to their health. Our research goal was to better understand how Indigenous parturients living in rural and remote communities conceptualised the risks associated with evacuation for birth before and during the COVID-19 pandemic. Methods To achieve this goal, we conducted semi-structured interviews with 11 parturients who travelled for birth during the pandemic and with 5 family members of those who were evacuated for birth. Results Participants conceptualised evacuation for birth as riskier during the COVID-19 pandemic and identified how the pandemic exacerbated existing risks of travelling for birth. In fact, Indigenous parturients noted the increased risk of contracting COVID-19 when travelling to urban centres for perinatal care, the impact of public health restrictions on increased isolation from family and community, the emotional impact of fear during the pandemic, and the decreased availability of quality healthcare. Conclusions Using Indigenous Feminist Methodology and Indigenous Feminist Theory, we critically analysed how mandatory evacuation for birth functions as a colonial tool and how conceptualizations of risk empowered Indigenous Peoples to make decisions that reduced risks to their health during the pandemic. With the results of this study, policy makers and governments can better understand how Indigenous Peoples conceptualise risks related to evacuation for birth before and during the pandemic, and prioritise further consultation with Indigenous Peoples to collaborate in the delivery of the health and care they need and desire.